Caracterização e aproveitamento de resíduos gerados na produção de etanol de segunda geração - Godoi, Isamara (2016)
Researches concerning the use of biomass lignocellulosic composition for second-generation ethanol production have received special attention as a possible contribution to energy sustainability. Although such activity has mainly used waste from the agricultural industry, it also generates other impactful solid and liquid wastes to the environment because they contain high concentrations of acids, alkaline and toxic elements. Thus, this trial aimed registering chemical characterization and recovering wastes generated in order to obtain a second-generation ethanol, particularly the precipitate produced during detoxification process by overliming hydrolyzed hemicellulose from sugarcane bagasse and liquid waste produced during cellulignin delignification phase in the pre-treatment to make the process of enzymatic saccharification of cellulose easier. Initially, the solid residue was submitted to physical and chemical analyses such as granulometric, analysis of metal compounds, content of inhibitory compounds to microbial activity such as acetic acid, furfural, hydroxymethylfurfural and phenols, sugars and moisture content. Waste potential determination as corrective of soil acidity was carried out by analyzing the attributes of corrective quality in soil (PN, PRNT), Ca and Mg and granulometry). Solid residue was also evaluated for its influence on bacterial communities by traditional microbiological techniques, bioassays with worms and lettuce seed germination. Liquid waste was characterized based on its metal contents present and inhibitory compounds. The lignin present in such liquor was precipitated with sulfuric acid and, after its characterization by infrared spectroscopy, was used as a biosorbent on lead ions adsorption in aqueous solution. The results have suggested that the waste generated during second-generation ethanol obtainment have some potential to become by-products to be applied in agricultural and environmental area. Lastly, the present trial has contributed to the production of bioethanol to be implemented in industry according to lignocellulosic biorefinery concept from an integrated model for a full biomass use in a sustainable management and correct disposal of the generated waste.